2016
DOI: 10.1021/acs.jmedchem.6b01265
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Potential Antimalarial Drug Candidate from a Series of 2-Aminopyrazines by Optimization of Aqueous Solubility and Potency across the Parasite Life Cycle

Abstract: Introduction of water-solubilizing groups on the 5-phenyl ring of a 2-aminopyrazine series led to the identification of highly potent compounds against the blood life-cycle stage of the human malaria parasite Plasmodium falciparum. Several compounds displayed high in vivo efficacy in two different mouse models for malaria, P. berghei-infected mice and P. falciparum-infected NOD-scid IL-2Rγ mice. One of the frontrunners, compound 3, was identified to also have good pharmacokinetics and additionally very potent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 14 publications
0
60
0
Order By: Relevance
“…Furthermore, the metabolic stability of this compound in dog and monkey models indicated the potential as a single‐dose cure for malaria. Accordingly, this compound is being prepared as a preclinical candidate . MMV085499 ( 465 ) is a 2‐aminopyrazine related to 463 and 464 which features in the malaria category of the Pathogen Box, but is currently unreported.…”
Section: Malariamentioning
confidence: 99%
“…Furthermore, the metabolic stability of this compound in dog and monkey models indicated the potential as a single‐dose cure for malaria. Accordingly, this compound is being prepared as a preclinical candidate . MMV085499 ( 465 ) is a 2‐aminopyrazine related to 463 and 464 which features in the malaria category of the Pathogen Box, but is currently unreported.…”
Section: Malariamentioning
confidence: 99%
“…Using previously acquired data, we assessed the solubility and in vitro metabolic stability of the most promising compounds from this study (Table ) . This data indicated that all compounds displayed good solubility in acidic media, with reduced solubility at pH 6.5, which presumably is a consequence of their inherent basicity.…”
Section: Resultsmentioning
confidence: 97%
“…However, bioisosteric replacement of the pyridine with a pyrazine resulted in a cohort of potent compounds with improved ADME characteristics, leading ultimately to the identification of 3 as a preclinical candidate…”
Section: Introductionmentioning
confidence: 99%
“…17 Further, cell-based medicinal optimization has led to the delivery of a clinical candidate, MMV390048 ( 1 ), a 2-aminopyridine, 21 and a preclinical development candidate, UCT943 ( 2 ), from the aminopyrazine class 22 (Figure 5). Our integrated screening cascade depicted in Figure 3 was critical in the selection and progression of these candidates and was propelled by the need to identify new chemical entities endowed with novel MoA and pan-activity against all parasite life cycle stages.…”
Section: Approaches To Novel Antimalarial and Anti-tb Leadsmentioning
confidence: 99%